THE CURRENT TASKS OF TEACHING VISUAL ART - B. A. Abdurasulova (Journals Park Publishing, 2023)
In the article, the general secondary education of visual arts the necessity of using the most effective methodical methods for the proper organization of lesson in schools, the formation of students’ thorough knowledge, skills and qualifications in this subject, and the innovations carried out in the field of education todey are highlighted.
Keywords: spirituality, education, outlook, visual arts, thinking, artistic taste, humanitarianism.